Batch adsorption studies for ketoprofen removal via Dillenia Indica peel activated carbon. Issue 1 (November 2021) - Fadzail, F; Hasan, M; Mokhtar, Z; Ibrahim, N; An, O S; Abidin, C Z A
Abstract: Removal of ketoprofen using Dillenia Indica peel activated carbon was investigated using batch adsorption at a laboratory scale. Chemical activation method with the aid of phosphoric acid was utilised in preparing the activated carbon. The adsorption experiments were evaluated using various factors which, are initial concentration, adsorbent dosage, and pH of ketoprofen. The optimum condition was determined to be at pH 6 and adsorbent dosage of 0.4 g with a most KTP uptake of 8.354 mg/g. The experimental findings showed that adsorption is favorable at lower pH. Isotherm studies were conducted and the data indicated that Langmuir isotherm was well fitted to the adsorption process and the pseudo-second-order model was more preferable in simulating the kinetic process. In essence, Dillenia Indica peel activated carbon was proven as being a favourable adsorbent for the uptake of ketoprofen in batch mode.